STRATEGIC IT-BUSINESS ALIGNMENT AS MANAGERSâ€™ EXPLORATIVE AND EXPLOITATIVE STRATEGIES - Masa’deh, Ra’ed (Mohâ€™d Taisir); Tarhini, Ali; Al-Dmour, Rand Hani; Obeidat, Bader Yousef (European Scientific Journal, ESJ, 2015)
It has been argued by many that firms in a dynamic environment are challenged to both explore new possibilities to survive in a changing business environment, and to exploit old certainties to secure efficiency benefits. Indeed, as the basic problem confronting an organization is to engage in sufficient exploitation to ensure its current viability and, at the same time, to devote enough energy to exploration to ensure its future viability. Besides managers and academics have recently become more aware of the need to understand how firms could manage exploration and exploitation. This research aims to investigate the literature within the concept of organizational learning orientations. This is done by viewing the definitions and distinctions of exploration and exploitation, how to manage the tension between the two strategies, how management could be organized to deal with exploration and exploitation at the managerial level, and finally ‘exploring’ the relationships between exploration and exploitation with performance. An early study conducted by Venkatraman (1989) described the concept of fit from six measurement perspectives: moderation, mediation, matching, gestalt, covariation, and profile deviation. However, the extant literature in MIS and management often uses the Strategic Alignment Model (SAM) of Henderson and Venkatraman (1993) to explain the ways that firms achieve alignment. Also, Papp (1995) proposed several perspectives for examining the business and IT strategies and infrastructures to determine if they work in harmony or in opposition.